Exploring the Dimensions of Millet Awareness among Generational Cohorts - Kunja , Sambashiva Rao; Deeksha Singh ,; Lipsa Das,; Kambhampati, Vivek; Naman Agarwal, (Indian Journal of Extension Education, 2025)
The rising disposable income and growing awareness of environmental sustainability have driven a shift towards healthier lifestyles across generational cohorts, with millets gaining popularity as a nutritious and sustainable food option. Although rural consumers adopt millet products in their regular diet, urban adoption seems limited. Therefore, the study explored millet awareness among urban consumers from Generations X (aged between 42-60 years), Y (28-42 years), and Z (18-28 years) using a qualitative approach, incorporating in-depth interviews and focus group discussions. The data was analysed through grounded theory methodology adopting the Gioia Technique. The findings revealed nine distinct types of millet awareness and highlighted variations across generational cohorts. Furthermore, the study identified four key dimensions of millet awareness, such as health-related awareness, product-specific awareness, environmental awareness, and socio-cultural awareness, thereby contributing to the existing body of knowledge. These insights provide valuable guidance for marketers, policymakers, and society to enhance awareness and adoption of millets, thereby promoting health, sustainability, and broader sustainable development goals.